DEVELOPMENT OF MULTILINGUAL E-TEXTBOOK ABOUT MADURA HISTORY FOR ELEMENTARY SCHOOL - Sumadi , Conny Dian; S, Ach. Kusairi (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This development research aimed to: (1) reveal the feasibility of the multilingual etextbook about Madura from material, media and language aspects (2) reveal the effectiveness of the multilingual e-textbook about Madura in learning process. Thisresearch refers to the developmental phases that were developed by Alessi and Trollip consisting of three development procedures, namely: (1) planning (2) design (3) development. This research produces multilingual e-textbook about Madura into three languages there are Bahasa, English and Bahasa Madura. The feasibility result score for content aspect was 4.23 (very decent), media aspect 4.24 (very decent) and language aspect was 4.24 (very decent). Affectivity test using learning outcome test, it is shown that 83.8% of the students able to solve the test more than the minimum score. Keywords: Multilingual, E-textbook, Madura History